Inkjet printed transparent and bendable patch antenna based on polydimethylsiloxane and indium tin oxide nanoparticles. Issue 12 (22nd September 2016) - Khan, Muhammad Arshad Hassan; Ali, Shawkat; Bae, Jinho; Lee, Chong Hyun
ABSTRACT: We propose a transparent and bendable inset microstrip patch antenna for 2.4 GHz wearable electronics applications. The proposed antenna is designed in high frequency structure simulator and realized by depositing indium tin oxide nanoparticles as a radiating patch and a ground on the polydimethylsiloxane substrate through Fujifilm Dimatix DMP‐3000 inkjet material printer at ambient conditions. On a flat position, the theoretical gain of the proposed antenna is 5.75 dBi, and its practical reflection coefficient ( S 11 ) is −25.9 dB. Under bending down to a diameter of 10 cm, the reflection coefficient is decreased up to 28.5%. It achieves the transparency of 91.5, 88, and 80% at thickness 1, 1.5, and 2 mm, respectively, and its restoration time is not more than 210 ms. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2884–2887, 2016